Comunicación pública y administración municipal. Una propuesta de modelo estructural - Campillo Alhama, Conchi (Pensar la Publicidad. Revista Internacional de Investigaciones Publicitarias, 2011)
Municipal administrations –by means of different communicative and relational processes- speak to the citizenship to transmit all kinds of messages related to the development of public competences. Those processes are grounded on the fundamental premise that citizens, as addressees of the local government action, must be informed of all those admininistrative actions and initiatives which may affect their condition of administered-citizens. Public communication becomes therefore a powerful tool in the hands of governing boards which let us explain, justify and thus legitimize the poticial decisions taken in every legislative period. The aim of this article is to propose a structural model of communication and relationship management which takes as a permanent reference the strategic territory plan and focuses on three main areas: institutional publicity, informative relationships and institutional relations.
Keywords: Communication; Municipal; Advertising; Thematization; Linkage; Model